Association Between Maternal Anemia and the Anthropometric Measurements of Full-Term Newborns - Kiran , Wajeeha; Babar , Habibullah; Noor , Mahal; Hussain , Muhammad; Ibrahim , Muhammad; Komal (Indus Journal of Bioscience Research, 2025)
Background: Anemia during pregnancy continues to be a serious public health concern, especially in poorer nations where it strongly increases mother and newborn morbidity and mortality. This study highlights the effect of maternal hemoglobin levels on fetal growth by examining the connection between maternal anemia and neonatal anthropometric measurements. Methods: From January 2024 to January 2025, a cross-sectional descriptive study was carried out at the Gynaecology and Obstetrics Department of a Quetta tertiary care hospital. A straightforward sample strategy was used to choose 300 full-term pregnant women between the ages of 18 and 40. Maternal anemia was classified as mild (10.9–9.0 g/dl), moderate (8.9–7.0 g/dl), and severe (<7.0 g/dl) according to WHO standards. Anemic and non-anemic groups were compared based on measurements of newborn anthropometric characteristics, including birth weight, length, head circumference, and chest circumference, taken within 24 hours of delivery. Findings: Of the 300 individuals, 48% had anemia, with moderate anemia accounting for the majority (78.5%). Height (48.2 ± 2.5 cm vs. 50.1 ± 2.4 cm), weight (2.85 ± 0.32 kg vs. 3.20 ± 0.35 kg), head circumference (33.4 ± 1.2 cm vs. 34.7 ± 1.3 cm), and chest circumference (32.1 ± 1.0 cm vs. 33.4 ± 1.1 cm) were all significantly lower in newborns of anemic mothers than in those of non-anemic mothers (p < 0.001 for all). Conclusion: There is a clear correlation between maternal anemia and poor neonatal anthropometric results. The growth and development of the fetus are greatly impacted by even slight anemia. To improve delivery outcomes and lower infant morbidity and death, these findings highlight the significance of early detection and management of maternal anemia by nutritional interventions, iron and folic acid supplements, and enhanced prenatal care.